Onset of Monsoon over India (MAUSAM, 1964)
The large-scale changes in the 5-day mean 700-mb contour pattern associated with the onset of monsoon rams over different parts of the country are located with the help of charts for  the period 1957-1962. The onset of monsoon over India and adjoining seas south of 15°N is associates with the disappearance of the premonsoon high over central parts of the country and the formation of the monsoon trough near 90°E at the 700-mb level, The formation of the monsoon low with the major axis in an east-west direction near about 20 N heralds the establishment of the monsoon over the entire country. Simultaneously the Pacific 'High' shifts northwards. It is also noticed that the extension of rains over central parts of the country is associated with the  disappearance of the anticyclonic curvature In the 700-mb contour pattern over the region. In those years in which the monsoon gradually extends westwards over north India such Its extension is associated with the gradual shift westwards of the monsoon trough.